Induction of Dbp by a histone deacetylase inhibitor is involved in amelioration of insulin sensitivity via adipocyte differentiation in ob/ob mice. (3rd July 2019) - Suzuki, Chisato; Ushijima, Kentaro; Ando, Hitoshi; Kitamura, Hiroko; Horiguchi, Michiko; Akita, Tomomi; Yamashita, Chikamasa; Fujimura, Akio
ABSTRACT: We previously reported that a histone deacetylase inhibitor (HDACi) increases D-site binding protein ( Dbp ) mRNA expression in adipose tissue and subsequently improved insulin sensitivity of obese (ob/ob) mice. However, the potential mechanism of this phenomenon was unclear. Thus, the aim of this study was to clarify the molecular mechanism involved in enhanced Dbp mRNA expression and improvement of insulin sensitivity in mice. Ob/ob mice were treated with HDACi every second day for 3 weeks. At the end of treatment, an insulin tolerance test was performed and epididymal adipose tissue obtained for fractionation into adipocytes and preadipocytes. HDACi improved insulin sensitivity in ob/ob mice and significantly increased Dbp mRNA in epididymal adipose tissue. Further, epididymal adipocytes of ob/ob mice showed a tendency towards a larger size distribution, while HDACi increased the proportion of smaller sized cells in fractionated preadipocytes. Dbp knocked-down 3T3-L1 cells down-regulated peroxisome proliferator-activated receptor-γ (PPAR-γ1) protein expression during adipogenesis, which suppressed adipocyte differentiation. These data indicate that DBP promotes adipocyte differentiation via direct up-regulation of PPAR-γ1 production in preadipocytes. In fractionated preadipocytes of ob/ob mice, DBP binding to the promoter region of the Ppar-γ gene and splicing variant of Ppar-γ ( Ppar-γ1sv ) mRNA expression were suppressed. HDACi significantly increased DBP binding to the Ppar-γ gene and Ppar-γ1sv transcription. Altogether, this indicates a modification in genetic regulation downstream from the circadian clock that can ameliorate an environmental function of adipose tissue, leading to improved insulin sensitivity in ob/ob mice.